Pengaruh Store Atmosphere dan Kualitas Pelayanan terhadap Loyalitas dengan Kepuasan Sebagai Variabel Intervening - Tamamudin; Sulaiman Helmi (Journal Of Islamic Economics And Finance, 2025)
The increasing intensity of business competition requires companies to continually innovate and prioritize customer satisfaction to foster long-term loyalty. This study aims to analyze the effect of store atmosphere and service quality on customer loyalty, with customer satisfaction as an intervening variable. This research employs a quantitative approach using a survey method, with data collected from 96 respondents through accidental sampling. Path analysis was utilized for data analysis using SPSS 23. The findings reveal that store atmosphere has a direct influence on both customer satisfaction and loyalty. In contrast, service quality does not significantly affect customer satisfaction but does directly impact customer loyalty. Furthermore, customer satisfaction does not directly influence loyalty but mediates the relationship between store atmosphere and customer loyalty. These results highlight the strategic importance of creating a positive store atmosphere to enhance shopping experiences and build emotional connections with customers. While service quality remains crucial, its impact on loyalty appears to be more direct than mediated through satisfaction. The study recommends that retail businesses focus on improving store atmosphere as a core component of their marketing strategy.